Incorporating Augmented Reality Tools into an Educational Pilot Plant of Chemical Engineering - Manuel J. Díaz; Carlos J. Álvarez-Gallego; Ildefonso Caro; Juan R. Portela (MDPI AG, 2023)
Chemical Engineering courses are often designed to be divided into two types of lessons: lecture and experimental. In the second one, students develop the knowledge in a hands-on way by attending a pilot plant equipped with different instruments. Hence, a thorough understanding of the different unit operations is needed and, therefore, the implications of changing the operational variables in a process. In this context, the use of new digital technologies is emerging as support tools with the aim of both improving the learning and the motivation of students. Specifically, Augmented Reality (AR) provides a modified physical environment overlaid with multimedia content in the form of text, graphics, video and/or audio. Thus, the incorporation of AR systems in the learning of science has proven to be useful, because it can present multiple benefits for students and teachers related to the improvement of spatial abilities, the increase of memory retention, the decrease of cognitive overload, and a boost in student motivation. This study has carried out a search for resources, projects, software, and applications to implement AR-based tools in the experimental sessions of a Chemical Engineering educational pilot plant. Based on all the information found, several AR projects were proposed by the teachers. Later, some of them were selected according to previously defined criteria and implemented as educational tools for students in the course called Experimentation in Chemical Engineering I. Finally, this tool was evaluated through subsequent post-surveys, being very positively rated by both students and teachers, mainly in the items related to helping to understand concepts or the operating procedures of the equipment.